Job competition amongst university graduates - Simonetta Longhi; Malcolm Brynin (University of Essex, Institute for Social and Economic Research (ISER), 2007)
We test whether in Great Britain the recent increase in the supply of university graduates has a negative impact on their wages, and analyse to what extent the local labour market for graduates should be seen as regional rather than national. We do this by computing two measures of job competition amongst graduates: the first assumes that the labour market for graduates is regional, while the second assumes that it is national. We then compare the two estimated wage impacts. We find that job competition amongst graduates has a negative impact on graduate wages, that the labour market for graduates appears to be regional, and that a large part of the regional imbalance between labour supply and demand is corrected by commuting rather than migration. Also, the wage impact of job competition seems to differ by gender and across groups of occupations.
Keywords: 330